What are we being told about how to teach games? A three-dimensional analysis of comparative research into different instructional studies in Physical Education and School Sports. (¿Qué sabemos acerca de la enseñanza de los juegos deportivos? Un análisis tridimensional de la investigación comparativa de diferentes estudios de enseñanza en Educación Física Escolar). - Alfonso Valero Valenzuela; Antonio Méndez Giménez; Ashley Casey (Ramón Cantó Alcaraz, 2010)
Abstract Determining what pedagogical approach could be most effective in delivering the desired learning outcomes in teaching games has been one of the more relevant concerns for physical education teachers, coaches and researches in the last few decades. Nevertheless, until recently, the research carried out in this field has been little profuse, has met with several difficulties and has been made from different perspectives, which has complicated its analysis altogether. The present study follows three main objectives: a) to analyse the nature of the interventions used in the comparative investigation directed to teaching sports, b) to determine the effects of the levels of treatment and, c) to outline some didactic consequences. Twenty comparative studies were selected for a systematic review. With regards to the instructional approaches the teaching of games three lines of analysis were contemplated: 1) Studies that compare interventions using the part- vs. whole-task teaching methods. 2) Studies that compare the teaching via direct vs. indirect instruction. 3) Studies that compare skills-based approach with alternative approaches, especially the direct instruction model versus the TGfU model. Based on the three paradigms, it was shown that the whole-task teaching method generates both greater satisfaction and security for children in their own performance. Indirect instructional techniques have a positive influence at an affective and social level, as well as on their decision making. The alternative approaches to the skills-based approach examined show that a greater degree of understanding of game play and more affective, and enjoyable behavior was obtained through tactics-based approach. The three-dimensional review reported in this paper could be used as complementary research to aid in future longitudinal studies such as the investigation that look at the integration of diverse instructional studies. Resumen Determinar qué aproximación pedagógica puede ser más eficaz para conseguir los resultados de aprendizaje deseados en la enseñanza de los juegos deportivos ha sido una de las preocupaciones más relevantes de profesores de educación física, entrenadores e investigadores en las últimas décadas. Sin embargo, hasta hace poco la investigación realizada en este campo ha sido poco profusa, ha contado con varias dificultades y ha sido abordada desde diferentes perspectivas, lo que ha dificultado su análisis en conjunto. El presente estudio pretende conseguir tres objetivos: a) analizar la naturaleza de las intervenciones empleadas en la investigación comparativa dirigida a la enseñanza deportiva, b) determinar los efectos de cada uno de los niveles de tratamiento y, c) extraer posibles implicaciones didácticas. Se realizó una revisión sistemática de los 20 estudios comparativos seleccionados. Se contemplaron tres líneas de análisis de la enseñanza de juegos deportivos: 1) Estudios que comparan los métodos analíticos versus métodos globales. 2) Estudios que comparan la enseñanza mediante instrucción directa versus búsqueda (indirecta), y 3) Estudios que comparan modelos tradicionales con modelos alternativos, en especial, el modelo técnico versus el modelo comprensivo (TGfU). Basándonos en los tres paradigmas señalados, se encontró que el método de enseñanza global genera mayor satisfacción y seguridad para los niños en su propio rendimiento. Las técnicas de enseñanza indirectas tienen una influencia positiva a nivel afectivo y social, así como en su toma de decisión. La aproximación alternativa a la enseñanza técnica mostró que se obtenía un mayor grado de comprensión del juego y un comportamiento más afectivo y mayor diversión mediante la aproximación basada en la táctica. Creemos que la revisión tridimensional divulgada en este artículo podría utilizarse como investigación complementaria para ayudar en estudios longitudinales futuros, por ejemplo, en la investigación que analiza la integración de diversos enfoques de enseñanza.